Taqdīm-Ta’khīr in Qur’anic Discourse: A Maqāṣidic Analysis of al-Baqarah 45 and 153 - Mustofa, Asrizal; Fauzi, Nurul Wahidah; Avicena, Fayiz Yan; Puteri, Fransischa Nayla (Mauriduna : Journal of Islamic Studies, 2026)
This study examined the function of taqdīm-ta’khīr (foregrounding and postponement) in Qur’ānic discourse through a maqāṣidī analysis of Q.S. al-Baqarah [2]: 45 and 153. The study was grounded in the importance of linguistic structure as an integral component of Qur’anic objectives, particularly in shaping ritual and ethical orientations. It aimed to explain why ṣabr (patience) is consistently positioned before ṣalāh (prayer) and to identify the higher objectives reflected in this syntactic arrangement. This research employed a qualitative library-based method using textual analysis rooted in Qur’anic rhetoric (balāghah) and maqāṣidī tafsīr, with attention to syntactic structure, discursive context, and objective orientation. The findings demonstrated that the precedence of ṣabr over ṣalāh is not merely rhetorical emphasis but a deliberate Qur’anic strategy for structuring religious priorities. In Q.S. al-Baqarah [2]: 45, ṣabr functions as an inner discipline that enables meaningful prayer and supports the preservation of religion (ḥifẓ al-dīn). In Q.S. al-Baqarah [2]: 153, ṣabr represents spiritual resilience during trials, oriented toward preserving human life and communal stability (ḥifẓ al-nafs). This study contributed to maqāṣidī Qur’anic studies by demonstrating that linguistic structure functions as an internal indicator of al-Qur’ān’s higher objectives.